PEMIKIRAN POLITIK ISLAM REVIVALISME/FUNDAMENTALISME: (PEMIKIRAN POLITIK AL-FARABI) - Aminuddin; Adelia Trisia (CV. Adiba Aisha Amira, 2024)
Al-Farabi's political thinking was heavily influenced by Western philosophers, especially Plato and Aristotle. For Al-Farabi, politics acts as ethics and initiative which are closely related to human happiness and welfare. AlFarabi began his political thoughts when discussing the origins and emergence of countries or cities. According to him, society arises from the existence of unity between individuals who need each other. This article aims to examine more deeply the Islamic political thought of Abu Nasir Muhammad bin al-Farakh al-Farabi, or often known as al-Farabi through the literature study method, which is a research method used to collect in-depth information and data through various literature, books, notes, magazines, journals and other references to identify Al Farabi's thoughts on politics, society, state and leadership.